Offers on definition of payments for lands of agricultural purpose (Journal of Geography and Environmental Management, 2019)
This article is devoted to system of the taxation of lands of agricultural purpose. Increase of a land tax on this categoryof lands is in the long term supposed. In this regard, the author studied experience of the taxation of lands in foreigncountries and on their basis offers on technique change definitions of land payments are given. Taking into accountoffers expected calculations of a land tax and a rent of agricultural producers are made.